Aquaporin-8 transports hydrogen peroxide to regulate granulosa cell autophagy - Huang, Binbin; Jin, Lingling; Zhang, Luodan; Cui, Xiaolin; Zhang, Zhen; Lu, Yongqi; Yu, Lujia; Ma, Tonghui; Zhang, He (Frontiers in Cell and Developmental Biology, 2022)
Aquaporin-8 (AQP8), a member of the aquaporin family, is strongly expressed in follicular granulosa cells, which could affect the hormone secretion level in female. AQP8, as a membrane protein, could mediate H2O2 into cells, thereby triggering various biological events. Deficiency of Aqp8 increases female fertility, resulting from the decrease of follicular atresia. The low cell death rate is related to the apoptosis of granulosa cells. However, the mechanism by which AQP8 regulates the autophagy of granulosa cells remains unclear. Thus, this study aimed to explore the effect of AQP8 on autophagy in follicular atresia. We found that the expression of autophagy marker light-chain protein 3 was significantly downregulated in the granulosa cells of Aqp8 knockout (Aqp8-/-) mice, compared with widetype (Aqp8+/+) mice. Immunofluorescent staining and transmission electron microscopic examination indicated that the number of autophagosomes in the granulosa cells of Aqp8-/- mice decreased. Using a follicular granulosa cell autophagy model, we verified that the concentration of H2O2 significantly increased during the autophagy of granulosa cells, consistent with the Aqp8 mRNA level. And intracellular H2O2 accumulation was modulated by endogenous AQP8 expression, indicating that AQP8-mediated H2O2 was involved in the autophagy of granulosa cells. AQP8 deficiency impaired H2O2 elevation through phosphorylated tyrosine activation. In addition, we carried out the analysis of transcriptome sequencing datasets in ovary and found there were obvious differences in principal components, differential expressed genes (DEGs) and KEGG pathways, which might be involved in AQP8-regulated follicular atresia. Taken together, these findings indicated that AQP8-mediated H2O2 transport could mediate the autophagy of granulosa cells. AQP8 might be a potential target for the diseases related to ovarian insufficiency.